Experimental auctions, collective induction and choice shift: willingness-to-pay for rice quality in Senegal - Demont, M.; Rutsaert, Pieter; Ndour, M.; Verbeke, W.; Seck, P.A.; Tollens, E. (Oxford University Press, 2013)
We propose a collective induction treatment as an aggregator of information and preferences, which enables testing whether consumer preferences for food quality elicited through experimental auctions are robust to aggregation. We develop a two-stage estimation method based on social judgement scheme theory to identify the determinants of social influence in collective induction. Our method is tested in a market experiment aiming to assess consumers' willingness-to-pay for rice quality in Senegal. No significant choice shift was observed after collective induction, which suggests that consumer preferences for rice quality are robust to aggregation. Almost three quarters of social influence captured by the model and the variables was explained by social status, market expertise and information